Comprehension and Knowledge - Naumov, Pavel; Ros, Kevin (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
The ability of an agent to comprehend a sentence is tightly connected to the agent’s prior experiences and background knowledge. The paper suggests to interpret comprehension as a modality and proposes a complete bimodal logical system that describes an interplay between comprehension and knowledge modalities.